Volume 6: Turbo Expo 2007, Parts a and B 2007
DOI: 10.1115/gt2007-27581
|View full text |Cite
|
Sign up to set email alerts
|

Time Resolved Investigations of an Axial Compressor With Casing Treatment: Part 1 — Experiment

Abstract: A casing treatment with axial and radial skewed slots ending in a plenum chamber has experimentally been investigated at a highly subsonic axial compressor stage. The aim was to investigate the physical phenomenon of this treatment family that is responsible for the stabilization of the blade passage flow and the drop in efficiency mostly observed. The experimentally gained performance results of this configuration showed an extension of the operating range by approximately 50%, while the efficiency for design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Casing treatment or placing a porous casing around the rotor tip is in effect a technique to control the casing boundary layers and thus delay the occurrence of the instabilities. This fact has been confirmed by several investigators [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Casing treatment or placing a porous casing around the rotor tip is in effect a technique to control the casing boundary layers and thus delay the occurrence of the instabilities. This fact has been confirmed by several investigators [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionsupporting
confidence: 69%
“…It was concluded from the above studies that an angle of skew of +45 ∘ would be most beneficial. Emmrich et al [15][16][17] carried out numerical and experimental analysis of a single stage subsonic compressor coupled with skewed casing treatment with a porosity of 67%. The slots were inclined to the axial direction by 15 ∘ and to the radial by 45 ∘ in the direction of rotation.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of numerical simulations can be found in the literature (e.g. Hathaway 2002, Zhu and Chu 2005, Emmrich et al 2007 discussing compressor performance as well as aerodynamic effects. In order to validate the numerical models applied for CFD, the demands on accuracy and spatial resolution for non-intrusive laser-based flow diagnostics are steadily increasing to match the continuous improvement of numerical simulation tools.…”
Section: Introductionmentioning
confidence: 99%
“…Emmrich et al [1] have investigated a highly subsonic axial compressor stage with casing treatment both experimentally and numerically for understanding the flow physics. Effect of casing treatment with axial and radial skewed slots for a high subsonic axial compressor stage, improved stall margin but with slight loss in efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…This revealed that in casing treatment delays vortex break down and helps in moving surge line to lower mass flows rates. Wilke and Kau [3] have shown that cavities or slots can successfully reduce the detrimental three-dimensional flow phenomena Fig.1 casing treatment slot on rotor tip region of a compressor blade [1] originating at the rotor tip gap. But the authors did not observe same effect at different design speeds with the tip in nearly subsonic conditions.…”
Section: Introductionmentioning
confidence: 99%